Kualitas Fisik dan Kimia Dedak Padi dengan Penggunaan Ekstrak Daun Mengkudu (Morinda citrifolia ) sebagai Bahan Pengawet Nabati - Ruslan, Ruslan; Hafsah, Hafsah; Mulyati, Mulyati (Mitra Sains, 2024)
The results showed that the interaction between the level of use of noni leaf extract and the treatment time was not significant (p>0.05) on the specific gravity and water content variables, but had a very large influence. significant effect (p<0.01) on the variables fat content, amount of feroxide and antioxidants). The specific gravity of the use of BHT preservative gives a value that is no different from the use of noni leaf extract vegetable preservative, the same thing also happens with the long storage treatment. The higher use of noni leaf extract in rice bran can significantly reduce the water content, crude fat and ferroxide levels, but can increase the antioxidant content. The conclusion from the results of this research is that the physical and chemical quality of rice bran can be maintained by using 0.03% noni leaf extract with a storage time of up to 42 days.